Answer:
y-intercept = -2
Explanation:
12x - 4y = 8
First, we want to put y on one side, so,
-4y = -12x + 8
Now we need to have y by itself without the -4, so,
y =
+
![(8)/(-4)](https://img.qammunity.org/2023/formulas/mathematics/college/ny6hv1ab1u29tsmf3kektgb2l3ai54e4r2.png)
Above the -12x and the -4 are both negative and are in a fraction, so, now we cross it out. This is because 2 negative signs make a positive.
y =
+
![(8)/(-4)](https://img.qammunity.org/2023/formulas/mathematics/college/ny6hv1ab1u29tsmf3kektgb2l3ai54e4r2.png)
Both the first and second fractions can now be simplified, so,
12 / 4 = 3 and 4 /4 = 1
8 / -4 = -2
The equation will now look like this
y = 3x - 2
The y-intercept of an equation is always at the end of the equation. In this case it is -2. This is because that is what we start with.
So, the y-intercept is -2.